A community-based approach to low-income residential energy efficiency participation barriers. Issue 12 (1st December 2016) - Reames, Tony Gerard
ABSTRACT: Financial barriers are often cited as the principle impediment to the adoption of energy efficiency measures. Since 1976, the US Department of Energy's Weatherisation Assistance Programme (WAP) has provided state block grants for no-cost, low-income energy efficiency retrofits. Yet, millions of low-income American households lack affordable, reliable, and efficient energy access. The American Recovery and Reinvestment Act of 2009 boosted WAP's annual appropriation from $230 million to $5 billion, requiring states to explore innovate approaches to quickly increasing programme participation. Community-based energy programmes have shown success for overcoming various barriers and increasing participation in the adoption of energy technologies. This case study explores a community-based approach to scaling WAP-funded energy efficiency retrofits in a cluster of five urban, low-income, majority African-American neighbourhoods, known as the Green Impact Zone (GIZ), in Kansas City, Missouri. Findings from interviews with GIZ stakeholders suggest that local context is important to how energy efficiency participation barriers manifest. The targeted, community-based approach to WAP created institutional capabilities for increased recognition of participation challenges and facilitated opportunities for alternative solutions that may otherwise have been overlooked under the standard self-referral implementation of WAP. Lastly, effective implementation of WAP required policy workarounds that recognised the unique characteristics and needs of the target community.